“Family 500+” programme as a social investment aimed at increasing the number of births in Poland – an analysis of Internet forums discourse - Michoń, Piotr (Studia Demograficzne, 2021)
The aim of the paper is to identify discourses related to the pro-natalist goal of the “Family 500 plus” programme, which is the largest family cash benefit scheme ever introduced in Poland. The paper presents an analysis of the conventional discourse based on Internet forums devoted to this programme. The analysis of 47 forums and over 3,000 posts shared between November 2015 and June 2019 allowed the author to distinguish fourteen dominant conventional discourses which were classified into three groups labelled as follows: (1) discourses of the state’s/individuals’ responsibility (2) discourses concerning policy making (3) discourses of (in)efficiency and (in)effectiveness. The research also indicates the leading role of the social perception of parents-beneficiaries in the debate on the “Family 500+” programme. The key to gaining social support, and, more broadly, for the legitimation of the welfare state in Poland, seems to care for a positive image of parents eligible for the benefit. The paper reveals complexity and interdependence of arguments concerning chances of the programme in terms of supporting increases in fertility in Poland. To the best of the author’s knowledge, this paper is the first attempt to analyse online forums in terms of social policy instruments.